2000
DOI: 10.2214/ajr.174.5.1741447
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Gadolinium-Enhanced MR Angiography of Vascular Complications After Liver Transplantation

Abstract: Three-dimensional gadolinium-enhanced MR angiography is useful in the examination of liver transplant patients and offers a noninvasive adjunct in patients with difficult or indeterminate sonographic examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…99 True fast imaging with steady state precession (true FISP) with MRI has been shown to be a useful adjunct to contrast enhanced MR angiography in severely debilitated patients, where respiratory motion may degrade the images or when the use of contrast medium is not possible due to poor venous access. 100 MR portography is valuable in determining the resectability of neoplasm involving the portal venous system 101 and follow-up after therapeutic procedures 102 including surgical splenorenal and mesocaval shunts. MR angiography has precluded the use of effective, but more invasive techniques like carbon dioxide portography or intraarterial digital subtraction angiography.…”
Section: Computed Tomography and Magnetic Resonance Imagingmentioning
confidence: 99%
“…99 True fast imaging with steady state precession (true FISP) with MRI has been shown to be a useful adjunct to contrast enhanced MR angiography in severely debilitated patients, where respiratory motion may degrade the images or when the use of contrast medium is not possible due to poor venous access. 100 MR portography is valuable in determining the resectability of neoplasm involving the portal venous system 101 and follow-up after therapeutic procedures 102 including surgical splenorenal and mesocaval shunts. MR angiography has precluded the use of effective, but more invasive techniques like carbon dioxide portography or intraarterial digital subtraction angiography.…”
Section: Computed Tomography and Magnetic Resonance Imagingmentioning
confidence: 99%
“…Therefore, a complete absence of flow in the main hepatic artery and a tardus parvus pattern in the intrahepatic branches of the hepatic artery are highly suggestive of hepatic artery thrombosis and should be confirmed with other imaging techniques (Hall et al, 1990). MR angiography is a useful and noninvasive method for evaluating the patency of the hepatic artery and may play an important role in identifying patients who require hepatic angiography (Glockner et al, 2000;Ito et al, 2000). When thrombosis is present, MR angiography accurately demonstrates the location of the thrombus by showing arterial opacification up to the thrombus, abrupt cutoff of the hepatic artery at the thrombus, and lack of opacification of distal branches ( Fig.…”
Section: Hepatic Artery Thrombosismentioning
confidence: 99%
“…and a body coil. After the localizing images were obtained, a breathhold T1-weighted fast multiplanar spoiled gradient-echo (FMPSPGR) sequence (repetition time/echo time, 150/4.2 msec; flip angle, 90°; field of view, 360 mm; matrix, 128×256; 18 slices; slice thickness, 7.0 mm; gap, 3.0 mm; one signal acquired) and a respiratory-triggered T2-weighted fast spinecho sequence (repetition time/echo time, 2800-4200/80 msec; echo train length [8][9][10][11][12] With T1-weighted and T2-weighted images as reference, the imaging volume of 3D CE MRA was acquired in a coronal plane to cover the hepatic veins, IVC, portal veins and collateral vessels. The imaging volume was determined by a radiologist depending on each patient´s abnormalities, liver size and ability of breathholding.…”
Section: D Ce Mra Examinationmentioning
confidence: 99%
“…However, some limitations are also existed in each of these modalities [2][3][4][5][6][7] . Three-dimensional contrast-enhanced magnetic resonance angiography (3D CE MRA) is a new technique and widely used in the imaging of the arterial system, portal venous system and central venous system [8][9][10][11][12][13][14][15][16] . However, to our knowledge, few studies have been reported so far concerning its use in the diagnosis of BCS [17] .…”
Section: Introductionmentioning
confidence: 99%